Intussusception after Laparoscopic Gastric Bypass Surgery: An Underrecognized Complication - Singla, Smit (Hindawi Publishing Corporation, 2012)
Introduction. Intussusception after bariatric surgery is an uncommon complication that is now being frequently reported. Most people consider dysmotility to be the causative mechanism in the absence of obvious etiology. Material and Methods. A worldwide search identified literature describing intussusception after bariatric surgery. We also included our own patients and analyzed information regarding demographic profile, risk factors, presentation, diagnosis, and post treatment course. Results. Seventy one patients were identified between 1991 and 2011. Majority of the affected patients were females (n = 70, 98.6%); median time to presentation after gastric bypass surgery was 36 months. Most patients presented with abdominal pain, nausea and vomiting, but without obvious peritonitis. Sixty eight patients (96%) required surgery; 48 (70.6%) underwent revision of anastomosis, 16 (23.5%) had reduction without resection, while 4 patients (5.9%) had plication only. Amongst these, most patients (n = 51, 75%) were found to have retrograde intussusception. Post-operatively, 9 patients presented with recurrence (range, 0.5–32 months). Five patients, who had earlier been treated without resection, eventually required revision of the anastomosis. There was no mortality noted. Conclusion. Intussusception after bariatric surgery is uncommon and its diagnosis is based on a combination of physicial, radiological and operative findings. An early surgical intervention reduces morbidity and prevents recurrence.